NAC Transcription Factors ANAC087 and ANAC046 Control Distinct Aspects of Programmed Cell Death in the Arabidopsis Columella and Lateral Root Cap - Huysmans, Marlies; Buono, Rafael Andrade; Skorzinski, Noemi; Radio, Marta Cubria; De Winter, Freya; Parizot, Boris; Mertens, Jan; Karimi, Mansour; Fendrych, Matyas; Nowack, Moritz K. (The Plant cell, 2018)
Programmed cell death in plants occurs both during stress responses and as an integral part of regular plant development. Despite the undisputed importance of developmentally controlled cell death processes for plant growth and reproduction, we are only beginning to understand the underlying molecular genetic regulation. Exploiting the Arabidopsis thaliana root cap as a cell death model system, we identified two NAC transcription factors, the little-characterized ANAC087 and the leaf-senescence regulator ANAC046, as being sufficient to activate the expression of cell death-associated genes and to induce ectopic programmed cell death. In the root cap, these transcription factors are involved in the regulation of distinct aspects of programmed cell death. ANAC087 orchestrates postmortem chromatin degradation in the lateral root cap via the nuclease BFN1. In addition, both ANAC087 and ANAC046 redundantly control the onset of cell death execution in the columella root cap during and after its shedding from the root tip. Besides identifying two regulators of developmental programmed cell death, our analyses reveal the existence of an actively controlled cell death program in Arabidopsis columella root cap cells.